School as a Dialogue Space towards Humanist Education: A Case Study of Frateran Catholic High School Surabaya - Renanthya, Eva (research, training and philanthropy institution Natural Aceh, 2025)
According to John Dewey, education forms fundamental abilities involving thought patterns and emotional power toward human character. The reality is that the practice of bullying, sexual violence, and acts of intolerance also colored the world of education in Indonesia, marked by increasing cases of violence and discrimination in schools in the period 2015-2023. Implementing the Merdeka Curriculum is seen as one way to humanize humans. Frateran High School, as one of the Catholic educational institutions, also takes part in efforts to humanize humans as an application of the teachings standard in the church document Educating to Fraternal Humanism. In addition to the three cardinal sins in education that must be avoided, students are currently faced with the challenge of increasingly diverse backgrounds of friends around them, such as those experienced by students after the opening of the dormitory in 2022. This research uses a qualitative method to analyze the data using Paulo Freire's theory of liberating education. This study found that the school implemented a culture of openness, allowing for spatial dialogue within the community. Restitutive culture in dealing with students, habituating dialogue, and using problem-based learning methods in learning are school strategies for building humanistic education.